A pilot study to detect von willebrand disease in women with menorrhagia - Yusof, Wan Aswani Wan (2007)
Von Willebrand disease (vWD) is the most common inherited bleeding disorders, found in approximately 1% of the general population, without ethnic differences. vWD results from a qualitative or quantitative defect in von Willebrand factor (vWF) resulting in impaired primary homeostasis. Menorrhagia is defined objectively as > 80ml menstrual blood loss per cycle or menses lasting longer than 7 days and is a common gynecologic problem in women of reproductive age. However, in 50% of cases, no pathology is detectable. Menorrhagia is valuable predictors of bleeding disorder in women. The frequency of vWD in women with menorrhagia ranges from 5-50% in different studies. The aim of this study is to know the prevalence of vWD in women with menorrhagia of unknown cause and identify the subtypes of the disease. Thirty women who came to Obstetric and Gynecology Clinic, HUSM with menorrhagia without uterine pathology was selected for this study. A detailed history related to menorrhagia was acquired from them. Full blood count (FBC), prothrombin time (PT), activated partial prothrombin time (APTT), ABO blood grouping, factor VIII activity (FVIII: C), von Willebrand factor antigen (vWF: Ag) and von Willebrand factor activity (vWF: Ac) and collagen binding assays (vWF: CBA) were measured in all patients. Subsequently ristocetin induced platelet aggregation (RIP A) was performed for those who had abnormal von Willebrand studies. Out of 30, 97% were Malay with median age of 42 years old. Four (13.3%) patients have abnormal parameters of von Willebrand studies. Two were diagnosed as 'possible' vWD Type 1, one patient as von Wille brand deficiency related to blood group 0 and the other one as 'possible' vWD Type 2 either subtype 2A or 2M. There is no association between age, onset of menorrhagia, dtmrtion of menstruation, history of blood transfusion or other bleeding tendencies with the development of the disease. Based on von Willebrand studies, von Willebrand functional assays (vWF: Ac and vWF: CBA) was significantly lower than vWF: Ag and FVIII: C in this 4 patients. Effect of hormone replacement therapy and blood group were analyzed and both did not show statistically significant in contributing to von Willebrand profiles. In conclusion, to date this is the first reported cases of vWD among Malaysian women with menorrhagia without uterine pathology. vWD is highly prevalence and though coagulation screening test is not helpful, we would like to suggest that a von Willebrand studies is directed to patient at least before planning for an invasive procedure.